2020
DOI: 10.1186/s12989-020-00350-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral toxicity of titanium dioxide P25 at repeated dose 28-day and 90-day in rats

Abstract: Background: Nanotechnology is indispensable to many different applications. Although nanoparticles have been widely used in, for example, cosmetics, sunscreen, food packaging, and medications, they may pose human safety risks associated with nanotoxicity. Thus, toxicity testing of nanoparticles is essential to assess the relative health risks associated with consumer exposure. Methods: In this study, we identified the NOAEL (no observed adverse effect level) of the agglomerated/aggregated TiO 2 P25 (approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…In rats orally exposed to TiO 2 NPs < 30 nm, inconsistent and/or unexplained sex differences in some parameters were reported (e.g. hypobilirubinaemia in females (Chen et al (2015a); heart rate and blood pressure changes in females (Chen et al (2015b); leucocyte changes in females (Heo et al, 2020); higher absolute pituitary weights in males (Heo et al, 2020); lower blood insulin levels in females, lower C-peptide levels in males and differences in blood concentrations compared to controls in a glucose tolerance test in males (Chen et al, 2020b). The Panel considered that the TG changes reported in several studies were likely incidental study findings since the reductions were seen in only one sex and without a clear dose response (Chen et al, 2015b), lacked a clear dose response (Vasantharaja et al, 2015) or increased in a single dose study (Grissa et al, 2015) The Panel considered that the effects reported in mouse studies with TiO 2 NPs < 30 nm could be associated with accumulation of NPs in various tissues whereas inconsistent findings in rats were considered incidental.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In rats orally exposed to TiO 2 NPs < 30 nm, inconsistent and/or unexplained sex differences in some parameters were reported (e.g. hypobilirubinaemia in females (Chen et al (2015a); heart rate and blood pressure changes in females (Chen et al (2015b); leucocyte changes in females (Heo et al, 2020); higher absolute pituitary weights in males (Heo et al, 2020); lower blood insulin levels in females, lower C-peptide levels in males and differences in blood concentrations compared to controls in a glucose tolerance test in males (Chen et al, 2020b). The Panel considered that the TG changes reported in several studies were likely incidental study findings since the reductions were seen in only one sex and without a clear dose response (Chen et al, 2015b), lacked a clear dose response (Vasantharaja et al, 2015) or increased in a single dose study (Grissa et al, 2015) The Panel considered that the effects reported in mouse studies with TiO 2 NPs < 30 nm could be associated with accumulation of NPs in various tissues whereas inconsistent findings in rats were considered incidental.…”
Section: Discussionmentioning
confidence: 99%
“…In rats orally exposed to TiO 2 NPs < 30 nm, inconsistent and/or unexplained sex differences in some parameters were reported (e.g. hypobilirubinaemia in females (Chen et al., 2015a); heart rate and blood pressure changes in females (Chen et al., 2015b); leucocyte changes in females (Heo et al., 2020); higher absolute pituitary weights in males (Heo et al., 2020); lower blood insulin levels in females, lower C‐peptide levels in males and differences in blood concentrations compared to controls in a glucose tolerance test in males (Chen et al., 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations